Digestible threonine-to-lysine ratio for piglets under health challenge (Research, Society and Development, 2020)
Aiming to determine the ration between digestible lysine and digestible threonine (Thr/Lys) for weaned piglets at 27 days, kept in the nursery under sanitary challenge conditions, 105 hybrid piglets with initial weight of 7.2 ± 0.41 kg, were distributed in randomized block design inside of five treatments (Thr/Lys ratios of 0.56; 0.63; 0.70; 0.77 and 0.84), seven replicates and three piglets per experimental unit. The Thr/Lys ratios did not affect (P>0.05) piglet performance. There was quadratic effect (P=0.02) of the Thr/Lys ratio on the protein/fat ratio and the estimated point of the bigger protein/fat ratio occurred with the Thr/Lys ratio of 0.68. The Thr/Lys ratio did not affect (P>0.05) the carcass parameters and serum urea levels, however, the liver and kidney weights raised with the increase (P=0.01) in Thr/Lys rate. The Thr/Lys ratio had a quadratic effect (P=0.01) on rate of plasma haptoglobin, Thr/Lys ratio was estimated at 0.74. It was concluded that the ratio between digestible threonine with digestible lysine for piglets from 27 to 48 days of age raised under sanitary challenge conditions is 0.74.